2003
DOI: 10.2166/wst.2003.0176
|View full text |Cite
|
Sign up to set email alerts
|

Fluid hydrodynamics in submerged and sidestream membrane bioreactors

Abstract: As with all membrane processes, turbulence, as promoted by aeration in submerged membrane bioreactors (MBRs) or pumping in sidestream (SS) systems to produce somewhat higher effective cross-flow velocities, increases mass transfer and reduces fouling. This is manifested in an elevated critical flux, the flux at which the membrane permeability is sustained. However, the non-Newtonian nature of the sludge makes precise rheological characterisation difficult. In this study, a calculation of the appropriate hydrod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Comparing to the industrial standards for high-quality potable reuse applications (bioreactor, clarifier, microfiltration, RO, and advanced oxidation), FOMBR systems (bioreactor, FO, and DS reconcentration) have a better potential for producing high-quality water with fewer processes, reduced footprint [61]. As seen by all membrane processes, turbulence promoted by aeration in submerged MBRs or by pumping in sidestream systems results somewhat higher effective cross-flow velocities increasing the mass transfer and reducing the fouling [62]. Some comparative operational parameters in FOMBR and conventional MBR are presented in terms of energy consumption in Table 1.…”
Section: Operation Modementioning
confidence: 99%
“…Comparing to the industrial standards for high-quality potable reuse applications (bioreactor, clarifier, microfiltration, RO, and advanced oxidation), FOMBR systems (bioreactor, FO, and DS reconcentration) have a better potential for producing high-quality water with fewer processes, reduced footprint [61]. As seen by all membrane processes, turbulence promoted by aeration in submerged MBRs or by pumping in sidestream systems results somewhat higher effective cross-flow velocities increasing the mass transfer and reducing the fouling [62]. Some comparative operational parameters in FOMBR and conventional MBR are presented in terms of energy consumption in Table 1.…”
Section: Operation Modementioning
confidence: 99%
“…Laborie et al (1998) reported that slug flow of air and water inside a hollow fibre can maintain stable permeate flux. Le-Clech et al (2003) studied the optimization of aeration in a submerged MBR defining minimum air velocity requirement. Nagaoka et al (2001Nagaoka et al ( , 2003 measured directly shear stress on a wall in bubble flows and concluded that interaction between bubbles and a wall could induce strong shear stress on a wall and is an important factor for submerged MBRs using flat-sheet membranes to maintain stable flux.…”
Section: Introductionmentioning
confidence: 99%
“…In this type of MBR configuration, the sludge is pumped from the bioreactor to the membrane module and air is introduced at the base of the membranes to achieve a two-phase slug flow in the vertical tubes by an appropriate choice of sludge and air flow rates (Le-Clech et al 2003.…”
mentioning
confidence: 99%